Stereochemie der [2.2]Metaparacyclophane - Fritz Vögtle; Peter Neumann (CHIMIA)
Stereochemistry of the [2.2]metaparacyclophanes. A brief description of the hitherto known carbocyclic and heterocyclic representatives of [2.2]metaparacyclophanes is given. The specific molecular geometry, steric effects, ring strain, molecular distortion and conformational mobility of this ring system are special topics in this paper.